The implementation of community development participation (KKN) based literacy education in Central Lombok - Muhammad Arief Rizka; Akhmad Sukri; Dira Permana (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2020)
This study aimed at analyzing the implementation of Thematic Community Service Program (KKN)-based basic literacy education of IKIP Mataram in the Central Lombok District which included registration, debriefing, implementation, monitoring, evaluation, and identification of the obstacles to implementation in the field. The research method used in this research was a descriptive method by combining quantitative and qualitative approaches. The subjects of this study were the Chairperson of Institute for Research and Community Service (LPPM) IKIP Mataram, the Organizing Committee, Community Service Students, Field Counseling Lecturers, Village Heads, and Literacy Education Students. Data collection instruments used were questionnaires, interviews, observation, and documentation guidelines. The data analysis technique used was qualitative and quantitative descriptive analysis. The results of this study showed that; (1) the implementation of basic literacy education based Thematic Community Service (KKN) Program at IKIP Mataram has been carried out through the stages of registration, debriefing, implementation, monitoring, and evaluation; (2) The results of the evaluation of the implementation of Basic Literacy Education learning have succeeded in teaching 802 illiterate people in Central Lombok district with data on the results of the basic literacy tests that have been carried out as many as 552 people have learned and declared passed and as many as 250 people declared not passed or do not yet meet the Minimum Completeness Criterion (KKM) of Basic Literacy Assessment; and (3) The main obstacle of the implementation of the Thematic KKN program is the earthquake disaster that struck the island of Lombok and has implications on the minimum residents basic literacy learning implementation in the field. However, Community Service (KKN) students with DPL assistance, the Village Head, and the LPPM Team have made an optimal effort so that the implementation of the Thematic KKN can continue to run in the community.